2015
DOI: 10.1007/s40265-015-0424-8
|View full text |Cite
|
Sign up to set email alerts
|

New and Emerging Treatments for Cystic Fibrosis

Abstract: Recently, a significant number of additional key medications have become licensed in Europe for the treatment of patients with cystic fibrosis (CF), including a number of inhaled antibiotics, such as nebulised aztreonam and dry powder versions of colistin and tobramycin for inhalation; dry powder inhaled mannitol, an agent to improve airway hydration and aid airway clearance; and ivacaftor, an oral therapy that directly acts on dysfunctional CFTR to correct the basic defect encountered in CF patients with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…ATP production levels by PAO1 and NH57388A were compared in MH and AS media with or without 2% OligoG CF-5/10. Cultures were prepared as for the growth curve experiments and analyzed using the BacTiter-Glo microbial cell viability assay (Promega) at 0, 2,4,6,8,12,24, and 48 h, with luminescence read on a Fluostar Omega plate reader.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ATP production levels by PAO1 and NH57388A were compared in MH and AS media with or without 2% OligoG CF-5/10. Cultures were prepared as for the growth curve experiments and analyzed using the BacTiter-Glo microbial cell viability assay (Promega) at 0, 2,4,6,8,12,24, and 48 h, with luminescence read on a Fluostar Omega plate reader.…”
Section: Methodsmentioning
confidence: 99%
“…The acquisition of MDR Pseudomonas in the CF lung has led to a resurgence of clinical interest in the bactericidal antibiotic colistin (24). Overlooked for many years due to associated nephro-and neurotoxicity (25,26), colistin is increasingly used to treat life-threatening infections (24) and as an inhaled therapy in CF to prevent establishment of infection by MDR bacteria (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-incubation of cells with gibberellin alone did not change p38 mRNA expression. When investigating the response of selected PNECs individually, we observed two different response types of CF PNECs, those in which the pre-treatment with gibberellin lead to an increase of IL-8 release (CF#7, 8,157) and those which showed a decrease in IL-8 release similar to non-CF cells (CF#12, 14,34). Analyses of p38 mRNA in these cells revealed that those in which gibberellin had a pro-inflammatory effect were PNECs with the higher basal p38 expression, while those which responded to gibberellin with a reduction in IL-8 had lower basal p38 mRNA expression.…”
Section: A20 As a Target For Anti-inflammatory Drug Development In Cfmentioning
confidence: 99%
“…However, although successfully improving expression and function of CFTR, airway inflammation was not reduced. In CF patients aged 6 years and above with Gly551Asp-CFTR, 6 months of treatment with Ivacaftor did not reduce inflammatory markers in sputum such as IL-1, IL-6 and IL-8 [7] and heterogeneous responses to the corrector/potentiator treatment have been reported in patients homozygous for Phe508del-CFTR [8]. This suggests that CFTR correction/potentiation may not directly improve the underlying compromised immune response, thus there is still an unmet need to normalise the inflammatory response in CF airways.…”
Section: Introductionmentioning
confidence: 98%